PERBANDINGAN METODE PEMBELAJARAN WHOLE PRACTICE DAN PART PRACTICE TERHADAP HASIL BELAJAR DRIBBLING BOLABASKET (STUDI PADA SISWA KELAS VII SMPN 1 JOGOROTO JOMBANG) - BAQIYUDIN, GALANG (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Dribble is one way to take the ball and can also help move the ball on the ground and away from the guard. If the game of basketball can not dribling then the game would be delayed even less likely to run. Many learning methods are used in order to improve students' ability in mastering the basic motion dribble. But in reality many students who have not been able to master these basic movements with the methods used by educators. From the research that has been established, it will be made a discussion of the results of the analysis of the research. The discussion here discuss the decomposition results of research on the implementation of this whole method of practice and part practice. Based on the results if the data from the study explained that both methods are applied to an impact on students, but part practice method gives better impact in the amount of 22.63% compared to the whole prctice the influence of only 12.86%. Keywords: Basic Dribble Movement, part practice method, method of whole practice, learning outcomes.